2006
DOI: 10.1021/jp060119f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Barium Loading on the Desulfation of Pt-BaO/Al2O3 Studied by H2 TPRX, TEM, Sulfur K-edge XANES, and in Situ TR-XRD

Abstract: Desulfation processes were investigated over sulfated Pt-BaO/Al2O3 with different barium loading (8 and 20 wt %) by using H2 temperature programmed reaction (TPRX), transmission electron microscope (TEM) with energy dispersive spectroscopy (EDS), sulfur K-edge X-ray absorption near-edge spectroscopy (XANES), and in situ time-resolved X-ray diffraction (TR-XRD) techniques. Both sulfated samples (8 and 20 wt %) form sulfate species (primarily BaSO4) as evidenced by S K-edge XANES and in situ TR-XRD. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…Time-resolved operando synchrotron-based studies (time-resolved x-ray diffraction) and EXAFS and XANES studies (Figure 4.3) clearly showed the mechanism of desulfation and thermal degradation of the fully formulated catalyst. The information obtained from these combined microscopy/spectroscopy/diffraction studies were essential to the successful introduction of this technology by Cummins Inc., in 2007-a remarkable example of detailed, fundamental, operando catalyst characterization leading to the development of a commercial technology (Kim et al 2006;Kwak et al 2009b). Pd on La-stabilized alumina: Recent work on Pd automotive catalysts revealed the unique role of La 2 O 3 .…”
Section: Ba/aluminamentioning
confidence: 99%
“…Time-resolved operando synchrotron-based studies (time-resolved x-ray diffraction) and EXAFS and XANES studies (Figure 4.3) clearly showed the mechanism of desulfation and thermal degradation of the fully formulated catalyst. The information obtained from these combined microscopy/spectroscopy/diffraction studies were essential to the successful introduction of this technology by Cummins Inc., in 2007-a remarkable example of detailed, fundamental, operando catalyst characterization leading to the development of a commercial technology (Kim et al 2006;Kwak et al 2009b). Pd on La-stabilized alumina: Recent work on Pd automotive catalysts revealed the unique role of La 2 O 3 .…”
Section: Ba/aluminamentioning
confidence: 99%
“…Sintering of the sulfate during sulfur circulation is controlled in such a form, and this control leads to improvement in sulfur desorption. It has been shown that the decomposition temperature is lowered when the particle size of generated sulfates is smaller [13], and it has also been reported that barium sulfate with a particle size of 3 nm or less is resolved easily at lower temperature [14]. Furthermore, using pore size controlled supports has been found to improve the decomposition of sulfates by physically inhibiting the sintering of the sulfate [30].…”
Section: Catalytic Performancementioning
confidence: 99%
“…Consequently, the deactivation of NSR catalysts depends on the amount of sulfur poisoning of the catalyst [12]. Sulfur deactivation also depends on the particle size of the sulfate produced by the NSR catalyst [13]. It has been reported that the decomposition temperature of sulfates decreases if the BaSO 4 particles in the catalyst are kept under 3 nm in size [14].…”
Section: Introductionmentioning
confidence: 99%
“…Desulfation of the accumulated SO x involves heating the catalyst to the temperature above 700°C or switching to a reducing atmosphere (CO or H 2 ) [12][13][14][15][16]. The main issue for the high-temperature desulfation is the loss of the catalytic activity caused by thermal aging (precious metal sintering and formation of BaAl 2 O 4 [17]).…”
Section: Introductionmentioning
confidence: 99%